Unusually large paraganglioma complicated with successive catecholamine crises: A case report and review of the literature - Huang, Zhenhui; Liang, Guojian; Shen, Hua; Hong, Chuyuan; Yin, Xuexia; Zhang, Shi (Frontiers in Surgery, 2022)
Background: Paragangliomas are rare neuroendocrine tumours that could secret catecholamines.Hypertensive crisis and heart failure caused by catecholamine crisis are fatal cardiovascular events.However,silent paragangliomas that lack typical symptoms of catecholamine pose a significant diagnostic challenge. Case Summary: A 45-year-old woman who presented with more than a one-year history of abdominal discomfort was suspected of having a gastrointestinal stromal tumour by a local hospital since a vast metastatic mass occupied her left abdomen.Thus,she was recommended to our hospital.After completing the gastroscopy, she unexpectedly developed acute heart failure and was transferred to the Intensive Care Unit (ICU)where the initial diagnosis of paraganglioma was considered through tortuous path.However,a second catecholamine crisis due to constipation led to acute heart failure again.After anti-heart failure therapy and rigorous preoperative preparation, surgery was arranged to remove the tumour.Postoperative pathology conﬁrmed the paraganglioma,and the patient was discharged from the hospital in good condition. Conclusion:We reported a rare case of huge retro-peritoneal paraganglioma with successive catecholamine crises and acute heart failure.This was probably the largest retro-peritoneal paraganglioma since the 1980s.Besides,we were the first to use surgical drawing to illustrate its complex anatomical adjacent relationship of retro-peritoneal paraganglioma.Our case emphasizes the inclusion of extra-adrenal paraganglioma in the differential diagnosis of retro-peritoneal tumours.In suspected paragangliomas,catecholamine testing is preferable to invasive procedures including gastroscopy and biopsy to avoid triggering a catecholamine crisis.Surgical resection is the primary treatment.We highlight the priority of dealing with the venous reflux branches of the tumour to prevent the release of catecholamines into the blood.In particular,preoperative preparation plays a vital role in managing paraganglioma.Moreover,it is necessary to schedule genetic testing and clinical follow-up due to the metastatic potential of paragangliomas.